2019
DOI: 10.3390/ijerph16132257
|View full text |Cite
|
Sign up to set email alerts
|

Examining Consumers’ Adoption of Wearable Healthcare Technology: The Role of Health Attributes

Abstract: With the advancement of information technology, wearable healthcare technology has emerged as one of the promising technologies to improve the wellbeing of individuals. However, the adoption of wearable healthcare technology has lagged when compared to other well-established durable technology products, such as smartphones and tablets, because of the inadequate knowledge of the antecedents of adoption intention. The aim of this paper is to address an identified gap in the literature by empirically testing a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
136
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(153 citation statements)
references
References 70 publications
16
136
1
Order By: Relevance
“…Studies of adoption behaviour circumscribing technology are considered a vital research area in the IT domain (Cheung et al 2019). Understanding the vital human factors influencing the use of ICT could lead to transformation of education systems in developing countries (Barakabitze et al 2019).…”
Section: Overview Of Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of adoption behaviour circumscribing technology are considered a vital research area in the IT domain (Cheung et al 2019). Understanding the vital human factors influencing the use of ICT could lead to transformation of education systems in developing countries (Barakabitze et al 2019).…”
Section: Overview Of Related Workmentioning
confidence: 99%
“…This is presumably because the users are not aware of its benefits. It is known from research study that adoption rate of an innovative technology would be enhanced if consumers realize its benefit (Cheung et al 2019). In terms of TAM (Davis 1989), the reason of this is the conception of 'Perceived Usefulness' (PU).…”
Section: Perceived Usefulness (Pu)mentioning
confidence: 99%
“…Many previous studies have found that perceived risk from privacy breaches affects people's satisfaction and thus affects their willingness to use [46]. Especially for emerging technologies, the risks posed by privacy issues will have a key impact on people's willingness to use them [47]. Currently, PM, as an emerging technology, has unclear data protection policies; thus, users may perceive a risk of privacy leakage.…”
Section: Technical Factors and Pm Adoption Intentionmentioning
confidence: 99%
“…User's medical technical knowledge included three items derived from Hairong Li, Daugherty, and Biocca [67]. Adoption intention included four items based on Cheung et al [47] and Venkatesh et al [18]. Seven-point Likert scales were used for all items.…”
Section: Measurementmentioning
confidence: 99%
“…TAM is one of the most widely used theoretical models that predicts the acceptance of information systems and communication technologies by individual users [20,21]. Over the years, TAM and its extended versions have been used to predict people's adoption of email [22][23][24], word processing and spreadsheet systems [25,26], e-commerce [27,28], social media such as Facebook, WhatsApp, Twitter, and WeChat [29][30][31], mobile fashion apps [32], personal digital assistants (PDAs) in health care [33], and mHealth [15,34].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%